Obatoclax inhibits alphavirus membrane fusion by neutralizing the acidic environment of endocytic compartments - Finny S Varghese; Kai Rausalu; Marika Hakanen; Sirle Saul; Beate M Kümmerer; Petri Susi; Andres Merits; Tero Ahola (ASM, 2022)
As new pathogenic viruses continue to emerge, it is paramount to have intervention strategies that target a common denominator in these pathogens. The fusion of viral and cellular membranes during viral entry is one such process that is used by many pathogenic viruses including chikungunya virus, West Nile virus, influenza virus etc. Obatoclax, a small-molecule antagonist of the Bcl-2 family of proteins was previously determined to be antiviral against influenza A virus and also Sindbis virus. Here, we report it to be active against alphaviruses like chikungunya virus (EC50 = 0.03 μM) and Semliki Forest virus (SFV) (EC50 = 0.11 μM). Obatoclax inhibited viral entry processes in an SFV temperature-sensitive mutant entry assay. Neutral red retention assay revealed that obatoclax induces rapid neutralization of the acidic environment of endolysosomal vesicles and thereby, most likely inhibits viral fusion. Characterization of escape mutants revealed that mutation L369I in the SFV E1 fusion protein was sufficient to confer partial resistance against obatoclax. Other inhibitors that target the Bcl-2 family of antiapoptotic proteins neither inhibited viral entry nor endolysosomal acidification, suggesting that the antiviral mechanism of obatoclax does not depend on its anticancer targets. Obatoclax inhibited the growth of flaviviruses like Zika virus, West Nile virus and yellow fever virus, which require low pH for fusion, but not of pH-independent picornaviruses like coxasackievirus A9, echovirus 6 and echovirus 7. In conclusion, obatoclax is a novel inhibitor of endosomal acidification preventing viral fusion that could be pursued as a potential broad-spectrum antiviral candidate.